(3eYGde GdOjf hedGP GdeLJgOjfs - (3GdYGedj, GdTGej, CHh efUhQ, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj Hf CMeO, J (B1011 (3g`s
(3ChdgG (B:s
... (3aTQYfG HJhajb Gddg JYGdi Edi JCdja gPG GdcJGH (B.. (3hLOOOfG Hg eYGgO GdeSGFd GdTQYjI hCMjjfG Hg eOGQS GdeHGMK (B( (3GdeSGFd UM (B) (3GdabgjI hTaYfG Hg JMQjQ GdaQhYg HJgPjH GdCUhd hLeYfG Hjf JMbjb GdOdjd hGdeOdhd (B....s
(3BNQgG (B:s
... (3ceG dG jNai Ydi GdeSGFd hjXgQ ef GdCUMGH gfG fhY GNJdGa aEf GdYdGeI bGd aj GdJgPjH dG jTJQW aj GdeSJZfj Ydeg Ydeg HUMI GLJgGO GdeaJj (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2/192s
(3EjVGM Gdecfhf (B2/505s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis